ANALISIS PENGARUH DEBT TO EQUTY RATIO DAN CASH CONVERSION CYCLE TERHADAP RETURN SAHAM PADA PT. BANK DANAMON INDONESIA, Tbk - Nurul Huda; Aris Munandar; M. Rimawan M. Rimawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this study are to determine the effect of Debt To Equty Ratio and Cash Conversion Cycle to stock is Return At PT. Bank Danamon Indonesia, Tbk. This research was used explanatory research by using sample survey approach. The sampling technique used is purposive sampling with 6 years (2010-2016) the number of samples on the financial report of PT. Bank Danamon Indonesia, Tbk. The technique of data analysis used is multiple linear regression. The results showed that the debt to equity ratio variable has no significant effect on stock return, cash conversion cycle variable has no significant effect on stock return, debt to equty ratio and cash conversion cycle have no significant effect on stock return at PT. Bank Danamon Indonesia, Tbk. Keywords: Dep To Equity ratio, cash conversion cycle, stock return